(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The State owes a primordial mandatory function to maintain the Law and order in the society by strict enforcement of the criminal law. Be it so, one should bear in mind that the criminal should be understood as a child of social necessity with an avowed purpose to be realised by the state in the interest of the public at large. It would be pertinent and significant to add in this context that the enforcement of the criminal is always guided by the peremptory norm of Rule of law which is the basic structure of the Indian Constitution. In India the Indian Penal Code and the code of criminal procedure, The Indian Evidence Act are the major substantive and procedural criminal laws as well as any other legislation made for the time being in force. A person arrested and detained by the police in their custody but subjected to injurious and oppressive treatment is virtually there by deprived of the fundamental right to life and personal liberty guaranteed by the constitution of India. The persons so arrested and confined in the police custody is still a person for all practical purposes therefore entitled to all the fundamental rights as well as the benefit of all privileges accorded by the constitution and statutes subject to the limitations of the law. As a corollary it emanates that the law enforcement process, exercise of statutory functions are there by governed by the rule of law. The investigating authorities should bear in mind fundamental proposition that they are governed and directed since the registration of F.I.R till the charge sheet is lodged before the competent court. The constitutional, statutory, and international framework envisages the administration of criminal justice should operate fairly adhering to the principle of fair play of justice. In fact, the Indian Judiciary (Apex) constitutionally created body is the custodian and protector of the rights and liberties of the people, upholding the supremacy of the constitution as well. Therefore, it has authority as well as a solemn duty constitution has imposed to redress the aggrieved in mates and issue necessary directions. As a matter of fact, the apex court has left no stone unturned in asserting their constitutional jurisdiction in multiple ways whenever the victims of custodial atrocities knocked the doors of the court and readily offered appropriate remedy. it has been consistently maintained by the supreme court in plethora of cases that the investigation of criminal cases tainted with custodial violence is repugnant to the fundamental right of life and personal liberty in as much as criminal justice is constantly monitored by the constitutional prescriptions and basic human rights enshrined international covenant on civil and political rights 1966. The menace of custodial violence is serious global menace; therefore, UNO has adopted convention against torture 1985. The Indian supreme court has by its judicial dynamism has broken fresh ground bye enlarging the scope of right to life and personal liberty in conformity with rule of law and human rights.